Effects of sulphur dioxide fumigation on Phleum pratense and vesicular-arbuscular mycorrhizal fungi - Clapperton, M Jill (The New phytologist, 1990)
Two experiments were conducted using controlled environment SO2 fumigation chambers which allowed only the shoots of Phleum pratense to be fumigated. Experiment 1 examined the effect of SO2 fumigation on the ability of vesicular-arbuscular (VA) mycorrhizal fungi to infect roots. Experiment 2 examined the effect of SO2 fumigation on the proliferation of VA mycorrhizas in the roots. There was a significant decrease in the amount of infection in the roots of plants exposed to SO2 . Low concentrations (0.05-0.07 μ 1-1 ) of SO2 affected the ability of VA mycorrhizal fungi to colonize and, also, to proliferate within roots. In both experiments, root colonization was the overriding factor affecting the number of tillers, leaf area, and shoot and root dry weights of infected plants. Increased VA mycorrhizal infection resulted in reductions in the plant growth parameters